Subarcsecond Imaging of a Solar Active Region Filament With ALMA and IRIS - da Silva Santos, J. M.; White, S. M.; Reardon, K.; Cauzzi, G.; Gunár, S.; Heinzel, P.; Leenaarts, J. (Frontiers in Astronomy and Space Sciences, 2022)
Quiescent filaments appear as absorption features on the solar disk when observed in chromospheric lines and at continuum wavelengths in the millimeter (mm) range. Active region (AR) filaments are their small-scale, low-altitude analogues, but they could not be resolved in previous mm observations. This spectral diagnostic can provide insight into the details of the formation and physical properties of their fine threads, which are still not fully understood. Here, we shed light on the thermal structure of an AR filament using high-resolution brightness temperature (Tb) maps taken with ALMA Band 6 complemented by simultaneous IRIS near-UV spectra, Hinode/SOT photospheric magnetograms, and SDO/AIA extreme-UV images. Some of the dark threads visible in the AIA 304 Å passband and in the core of Mg II resonance lines have dark (Tb<5000 K) counterparts in the 1.25 mm maps, but their visibility significantly varies across the filament spine and in time. These opacity changes are possibly related to variations in temperature and electron density in filament fine structures. The coolest Tb values (<5000 K) coincide with regions of low integrated intensity in the Mg II h and k lines. ALMA Band 3 maps taken after the Band 6 ones do not clearly show the filament structure, contrary to the expectation that the contrast should increase at longer wavelengths based on previous observations of quiescent filaments. The ALMA maps are not consistent with isothermal conditions, but the temporal evolution of the filament may partly account for this.